Fiscal Determinants of Empowerment - Raich, Uri (World Bank, Washington, DC, 2012)
Empowerment of local governments and citizens is a primary object of decentralization. Using the analytic lens of empowerment, the author explores the nature of decentralized governance and how this type of structure is likely to be more or less empowering. His primary concern is fiscal decentralization, specifically the association between fiscal determinants and the degree of empowerment of both citizens and local governments. The author's main argument is that both the revenue and expenditure characteristics of local public finances have an effect on the degree of empowerment. His hypothesis is that in a context of decentralized local governance, empowerment is most likely to occur when three conditions prevail: low costs of participation, large and flexible budgets, and a high proportion of tax revenues from a local base. But these ingredients for empowerment will not necessarily produce outcomes that are progressive and pro-poor. The author contrasts the intrinsic and the instrumental approaches to empowerment, but he does not assess the impact of empowerment on instrumental outcomes. For this hypothesis to support an instrumentalist perspective on empowerment, further empirical work must be conducted.